Assessment of sentinel lymph node biopsy after neoadjuvant chemotherapy for breast cancer in two subgroups: Initially node negative and node positive converted to node negative – A systemic review and meta-analysis - Alireza Shirzadi (Journal of Research in Medical Sciences, 2019)
Background: Neoadjuvant chemotherapy (NAC) is increasingly used to treat patients with breast cancer, but the reliability of sentinel lymph node biopsy (SLNB) following chemotherapy is in doubt. In this meta-analysis, we aimed to evaluate studies that examine the results of SLNB after NAC to assess identification rate (IR) and false-negative rate (FNR). Materials and Methods: Systemic searches were performed in the PubMed, ISI Web of Sciences, Scopus, and Cochrane databases from January 1, 2000, to November 30, 2016, for studies of SLNB after NAC for breast cancer and followed by axillary lymph node (LN) dissection in two subgroups: initially node negative and node positive converted to node negative. Two reviewers independently review quality of included studies. A random-effects model was used to pool IR and FNR with 95% confidence intervals (CI), and heterogeneity among studies was assessed by I2 and Q-test. Results: A total of 23 studies with 1521 patients in the initially node-negative subgroup and 13 studies with 1088 patients in the node-positive converted to node-negative subgroup, were included in this meta-analysis with IR and FNR of 94% (95% CI: 92–96) and 7% (95% CI: 5–9) in the initially node-negative subgroup and 89% (95% CI: 85–94) and 13% (95% CI: 7–18) in the node-positive converted to node-negative subgroup, respectively. Conclusion: Our meta-analysis showed acceptable IR and FNR in initially node-negative group and it seems feasible in these patients, but these parameters did not reach to predefined value in node-positive converted to node-negative group, and thus, it is not recommended in these patients.